The effect of foreclosure on Boston public school student academic performance - Katharine Bradbury; Mary A. Burke; Robert K. Triest (Federal Reserve Bank of Boston, 2013)
Although the recent wave of mortgage foreclosures has clearly been accompanied by economic hardship, relatively little research has examined how foreclosures affect the academic performance of students. This paper investigates the relationship between mortgage foreclosures and the academic performance of students using a unique dataset that matches information on the standardized test scores and attendance of individual Boston Public School students with real estate records indicating whether the student lived at an address involved in foreclosure and whether that student's parent or guardian was the owner or a tenant in the property. Econometric analysis of this relationship suggests that foreclosures are associated with slightly lower test scores and attendance, controlling for the previous-year's test score and attendance as well as other student characteristics and environmental factors. The results suggest that both the foreclosure event and the diminished student outcomes stem from underlying economic stress within the family. School changes during the school year, which are sometimes induced by foreclosure-related residential moves but also occur independently of foreclosure, may be associated with more substantial negative effects on academic performance than foreclosures, although this causal relationship is not certain. This latter finding suggests that policies that decouple residential moves from school changes during the school year may help to mitigate this indirect effect of foreclosure on student performance.
Keywords: I20; I24; J24; G21; 330